Impact of Race and Ethnicity on Weight-Loss Outcomes in Pediatric Family-Based Obesity Treatment - Eichen, Dawn M. (J Racial Ethn Health Disparities, 2020)
INTRODUCTION: Minority children are disproportionately affected by obesity and little is known about how race/ethnicity impacts outcomes in pediatric weight-loss treatment. This study aimed to evaluate whether race/ethnicity affected weight-loss outcomes in a pediatric obesity intervention. Secondary aims included evaluating whether race/ethnicity was associated with energy intake, exercise, program adherence, acceptability and attendance. METHODS: 150 parent/child dyads (age 8–12 years, BMI% 85–99.9; 32% Hispanic, 24% Non-Hispanic, Non-White, 44% Non-Hispanic White) participated in a randomized control trial evaluating weight loss in family-based behavioral treatment with (FBT) or without child participation (i.e., Parent-Based Treatment; PBT). Assessments occurred at baseline, mid-treatment (month 3) post-treatment (month 6) and follow-up (month 12 and 24). Analyses included linear mixed effect models, linear models and a negative binomial model. RESULTS: Weight loss in Hispanic, Non-Hispanic White, and Non-Hispanic, Non-White children was not significantly different by race/ethnicity at month 6, 12, and 24 (p = .259) and was similar across both treatments (FBT = −0.16 BMIz; PBT= −0.21 BMIz; p =.61). There were no differences in energy intake, physical activity, acceptability ratings or adherence to treatment (as measured by a post-treatment survey) (p’s >.123). However, Hispanic families attended fewer treatment visits than Non-Hispanic White families (p = .017). CONCLUSION: On average, children lost weight participating in our pediatric obesity treatment and there was no statistical difference in weight loss between groups. Future research evaluating whether culturally-adapted treatments would be more effective for racial/ethnic minorities or whether the personalization inherent in family-based behavioral treatment may be sufficient is needed.